(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
The collections of short stories La mitad del diablo (2006) y El juego del diábolo (2008) were conceived by its author, Juan Pedro Aparicio, as complementary works. Between both volumes there is a dialogue that starts from its structure and transcends each of its hyper-short fictions. This model of Quantum Literature tries to reveal and isolate the minimum essence of narrative microtexts or literary quanta; In accordance with this terminology, a sample of minifictions framed in their corresponding intertextual categories is presented: biblical quantum, mythological quantum, quantum tales, quantum-narrative, quantum-poetic and quantum-quantum, transtextuality quantum, metalliterature quantum and quantum intratextuality.